The Symbolic Meaning In Minangkabau Bukittinggi Traditional Wedding : Semiotics Studies - Nur Fadilla; Mayasari Mayasari; Hidayati Hidayati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Minang or Minangkabau is an ethnic cultural group that adheres to a distinctive customary system, namely the family system according to female lineage which is called the matrilineal system. In Minangkabau culture, marriage is one of the important events in the life cycle and is a very significant transitional period in forming a new small family group for offspring. The purpose of this research is to find out the symbolic meaning in Minangkabau traditional marriage. This research uses a qualitative method and uses the Peirce’s theory. The informants of this study are people who understand Minangkabau culture, such as the coconut of the Minangkabau tribe. Data collection techniques through observation and direct interviews to the field and obtain information from several books and websites. the results obtained were: maminang (applying), rapek sumando (consultation of traditional leaders), malam bainai (attaching henna to the bride), Manjapuik marapulai (picking up the groom), basandiang (side by side). Then the researcher compiles, describes, and writes the symbolic meanings that exist in the traditional Minangkabau wedding steps.